The Life and Thought of Louis Lowy : Social Work through the Holocaust - Gardella, Lorrie Greenhouse (Religion, theology, and the Holocaust., 2011)
Louis Lowy (1920-1991), an international social worker and gerontologist, rarely spoke publicly about the Holocaust. During the last months of his life, however, he recorded an oral narrative that explores his activities during the Holocaust as the formative experiences of his career. Drawing on Lowy's oral narrative and accounts from three other Holocaust survivors who witnessed his work in the Terezin ghetto and the Deggendorf Displaced Persons Center, Gardella offers a rich portrait of Lowy's personal and professional legacy. In chronicling his life, Gardella also uncovers a larger story about Jewish history and the meaning of the Holocaust in the development of the social work profession.